2008
DOI: 10.1021/la801814u
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling Properties of Poly(methyl methacrylate) Films Grafted with Poly(ethylene glycol) Monoacrylate Immersed in Seawater

Abstract: Biofouling of all structures immersed in seawater constitutes an important problem, and many strategies are currently being developed to tackle it. In this context, our previous work shows that poly(ethylene glycol) monoacrylate (PEGA) macromonomer grafted on preoxidized poly(methyl methacrylate) (PMMAox) films exhibits an excellent repellency against the bovine serum albumin used as a model protein. This study aims to evaluate the following: (1) the prevention of a marine extract material adsorption by the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Amphiphilic systems take advantage of the protein-resistant characteristics of hydrophilic materials that deter biofouling. 11 Polyethylene glycol (PEG) is one of the commonly investigated materials as it resists protein absorption and possesses non-toxic and nonimmunogenic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic systems take advantage of the protein-resistant characteristics of hydrophilic materials that deter biofouling. 11 Polyethylene glycol (PEG) is one of the commonly investigated materials as it resists protein absorption and possesses non-toxic and nonimmunogenic properties.…”
Section: Introductionmentioning
confidence: 99%
“…1 2 However, the primary method of adhesion involves spreading of an adhesive consisting of a complex protein or glycoprotein. 16 Surfaces modified with polyethylene glycol (PEG) are of great interest mainly due to their ability to resist protein adhesion. 17 PEG-based materials tend to prevent biofoulant settlement and adhesion via hydrophilic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that adsorbed proteins play a key role in the performance of medical devices because they influence animal cell adhesion, 13 microbial infections, 47 calcification, 8 and tissue integration. 9 Additionally, the study of interfacial proteins is of growing importance in the areas of biosensors, 10 biofouling, 11 immunology, 12 and a host of biological processes. 1315 …”
Section: Introductionmentioning
confidence: 99%